Seed-assembly-mediated fabrication and application of highly branched gold nanoshells having hollow and porous morphologies. (19th January 2022) - Park, Tae-Hyeon; Jeong, Dong-Won; Lee, Jung Ho; Jang, Du-Jeon
Abstract: Highly branched gold nanoshells (BAuNSs) having hollow and porous morphologies have been fabricated via a seed-assembly-mediated strategy. Gold seed assemblies can be prepared by removal of SiO2 nanotemplates with help of polyvinylpyrrolidone (PVP) molecules, which weakly link gold nanoparticles together even after SiO2 etching. L-3, 4-dihydroxy phenylalanine (L-DOPA) and AgNO3 are employed as shape-directing agents to induce the anisotropic growth of gold. BAuNSs exhibit 7.4 and 4.4 times stronger activities than SiO2 @Au nanoparticles in catalysis and surface-enhanced Raman scattering (SERS) applications, respectively, due to their large surface areas and numerous hot spots. It is necessary to find the optimal amount of gold deposition in fabrication to effectively utilize the hollow and porous morpologies of BAuNSs for catalysis and SERS applications. Overgrown nanobranches can fill the nanopores and nanogaps of BAuNSs, resulting in decrease of activities in applications. Overall, the seed-assembly-mediated fabrciation can be employed to produce plasmonic nanostructures having unique morphologies and high application activities.